EMOTIONAL DEPENDENCY IN STUDENT-TEACHER RELATIONSHIPS: ENHANCING INCLUSIVE EDUCATION SERVICES FOR PRESCHOOL STUDENTS (Proceedings of International Conference on Special Education, 2025)
Emotional dependency in student-teacher relationships (STR) is often overshadowed by the focus on closeness and conflict, leading to limited conceptual clarity, particularly in inclusive classrooms. Teachers frequently interpret dependency through behaviors perceived as disruptive or developmentally inappropriate, making it a complex phenomenon to navigate. Emotional dependency is important for special educational needs (SEN) students as it provides emotional security, supports self-regulation, promotes social and academic engagement and bridges communication gaps. This qualitative case study examines the perspectives of three preschool teachers on emotional dependency and the strategies they employ to manage it. Data were gathered through semi-structured interviews, guided by the Student-teacher Relationship Scale, the Classroom Assessment Scoring System, and relevant literature. Findings reveal that emotional dependency manifests as a child's need for emotional support, reassurance, and warmth from a trusted adult. Teachers foster secure relationships by acknowledging emotions, promoting self-regulation, and gradually encouraging autonomy through choice-based interactions. Notably, students with special educational needs exhibit heightened emotional dependency, necessitating adaptive and individualized strategies. This study highlights the critical role of educators in balancing emotional security and autonomy to create an inclusive and supportive learning environment, ensuring that all preschoolers, particularly those with special educational needs, receive the necessary emotional scaffolding for their development.